PENGARUH BAURAN PEMASARAN (KUALITAS PRODUK, HARGA, PROMOSI DAN SALURAN DISTRIBUSI) TERHADAP KEPUTUSAN PEMBELIAN YAMAHA NMAX DI SEMARANG - Purba, Novi Anathasia; Saryadi, Saryadi (Jurnal Ilmu Administrasi Bisnis, 2016)
This research is aimed to identify the effect of marketing mix: product, price, promotion and distribution on Yamaha NMAX purchasing decission in Semarang whether as parcial effect and as simultan effect. The type of research is explanotory research with 97 respondents which calculated using purposive sampling technique. Instrument data collection technique is by questionnaire and interview. Data were analyzed using liner regression analysis by SPSS For Windows. This research concludes that product, price, promotion, and place have positive and significant influence on puchasing decission partially. Furthermore, marketing mix has a positive and significant influence on puchasing decission and product is the most siginificant variabel. Concumer perseption of product, price, promotion and distribution are in good category. Then, purchasing decission is in high level. So, advice that can be given for PT. Yamaha Motor Manufaktur Indonesia is to improve that good perception higher with variate the product, use brand ambassador, fullfill the need fast, and provide new distributions channel.